2010
DOI: 10.1051/limn/2010026
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of littoral macroinvertebrates within extensive reed beds of a lowland pond

Abstract: -Although habitats of hard emergent macrophyte beds, including reed beds (Phragmites australis), are very common in the littoral zones of stagnant waters in central Europe, research investigating their macroinvertebrate communities is still lacking. In this study, the spatial distribution of macroinvertebrates was studied within large reed beds in the littoral zone of a lowland fishpond (Nesyt, SE Moravia, Czech Republic). Using a hand net, horizontal line transects in the reed bed leading from the marginal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 34 publications
(37 reference statements)
7
27
1
4
Order By: Relevance
“…De acuerdo con TUNDISI y MATSUMURA-TUNDISI (2008) y SYCHRA et al (2010), los cambios en profundidad ejercen influencia en la distribución de la macrofauna entre las raíces de las macrófitas, contribuyendo de esta forma a diferentes distribuciones de abundancia y riqueza, como las observadas en la presente investigación.…”
Section: Discussionunclassified
“…De acuerdo con TUNDISI y MATSUMURA-TUNDISI (2008) y SYCHRA et al (2010), los cambios en profundidad ejercen influencia en la distribución de la macrofauna entre las raíces de las macrófitas, contribuyendo de esta forma a diferentes distribuciones de abundancia y riqueza, como las observadas en la presente investigación.…”
Section: Discussionunclassified
“…Estes táxons costumam apresentar elevada riqueza nos ecossistemas de água doce e, em particular, na fauna fitófila (LEARNER et al, 19 8;PINDER, 1986;RODRIGUES et al, 2013), sendo também dominantes em bancos de macrófitas aquáticas (PEARSON;MATTHEWS, 1995;TRIVINHO-STRIXINO et al, 2000;KOUAMÉ et al, 2011;MARTINS et al, 2011) onde encontram boa disponibilidade de recursos alimentares na forma de detritos orgânicos aderidos às raízes. Outras variáveis ambientais da lagoa, como, por exemplo, maior adensamento das macrófitas, proximidade das raízes do vegetal com áreas de águas abertas ou fechadas e modi cações da profundidade da lagoa, poderiam também ter in uenciado na distribuição desta macrofauna entre as raízes, contribuindo para diferentes distribuições de riqueza (SYCHRA et al, 2010).…”
Section: Discussionunclassified
“…In our study, Oligochaeta comprised 15% of the total drift and most of them were found interwoven with bryophytes. Although most of them reach macrofaunal dimensions, some Naididae and Enchytraeidae are recognized as meiofaunal members living as epibenthos in phytal (Giere 2009), inhabiting aquatic macrophytes (Neiff & Caringnan 1997;Phillips 2008) and bryophytes (Sychra et al 2010), feeding mostly on bacteria and diatoms (Harper et al 1981;Bott & Borchardt 1999).…”
Section: Faunal Drift Compositionmentioning
confidence: 99%